1992
DOI: 10.2307/2937117
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in Population Change and the Organization of the Insect Community Associated with Goldenrod

Abstract: The extent to which insect communities are organized is poorly understood because few studies have examined both population-level processes and community-level patterns. Furthermore, our view of phytophagous insect populations is probably biased by the more frequent attention given to economic pests whose dynamics might be expected to be somewhat exceptional. Herein, we report on the population dynamics and community-level features in a diverse, native fauna of phytophagous insects associated with goldenrod (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
192
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(198 citation statements)
references
References 77 publications
(149 reference statements)
4
192
2
Order By: Relevance
“…In later succession, Carson & Root (2000) found that the outbreak of the leaf beetle M. vittata specializing on goldenrod S. altissima destroyed an old-field canopy dominated by goldenrods, thereby increasing the abundance of woody species and speeding plant succession from the herb-dominated to the treedominated stage. In a survey of 16 sites over six years, the same few species were dominant across all sites; notably the leaf chewer T. virgata, the leaf miner M. vittata, and the sap-feeder P. spumarius (Root & Cappuccino, 1992).…”
Section: Paradigms Lost Paradigms Gainedmentioning
confidence: 99%
“…In later succession, Carson & Root (2000) found that the outbreak of the leaf beetle M. vittata specializing on goldenrod S. altissima destroyed an old-field canopy dominated by goldenrods, thereby increasing the abundance of woody species and speeding plant succession from the herb-dominated to the treedominated stage. In a survey of 16 sites over six years, the same few species were dominant across all sites; notably the leaf chewer T. virgata, the leaf miner M. vittata, and the sap-feeder P. spumarius (Root & Cappuccino, 1992).…”
Section: Paradigms Lost Paradigms Gainedmentioning
confidence: 99%
“…T. virgata is an outbreak insect that can be a major defoliator of S. gigantea and related species in North America. 21 We grew plants originating from 10 populations in the US and 20 populations in Europe in common gardens at the University of WisconsinMilwaukee Field Station in Saukville, Wisconsin. There were five plant origincytotype combinations: three cytotypes from the US and two from Europe.…”
mentioning
confidence: 99%
“…In the Finger Lakes Region of New York alone, Root & Cappuccino (1992) documented 138 species of insects that feed on leaves, stems, or sap of tall goldenrod, Solidago altissima L. With its prodigious flowering display in late summer and early autumn, S. altissima is also visited by numerous species of pollen-, nectar-, flower-, and seed-feeding insects (Gross and Werner 1983;Sholes 1984). Therefore, I was not surprised during my studies of goldenrod in Virginia to see adults of the red-spotted purple, Limenitis arthemis astyanax, making repeated visits to S. altissima in early September-until I realized that the plants had yet to open any flowers.…”
Section: Limenitis Arthemis Astyanax (Fabricius) (Nymphalidae) Sippinmentioning
confidence: 99%